Implementation of a Computer-Based Accounting System and its Influence on Employee Performance at Grapari Telkomsel Jember - Galuh Ambarwati; HP Agustin; Lia Rachmawati (Medikun Publisher, 2024)
This research was carried out to find out how to implement a computer- based accounting system and its effect on employee performance at Grapari Telkomsel Jember. This research uses a qualitative research strategy that focuses on in-depth observation. The aim of this research was to find out whether the implementation of a computer-based accounting system had an effect on employee performance at GraPARi Jember. From the results of interviews conducted with 3 sources, namely Claudia and Fadelis as team leaders, Vira Vita as CSR, it was found that the use of a computer-based accounting information system affects employee performance at GraPARi. The use of a computer-based accounting system improves the performance of existing employees, making work fast and efficient in using available time and meeting appropriate targets